2020
DOI: 10.1038/s41598-020-60198-w
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Ion Conductivity in Superionic IL-Impregnated Metal-Organic Frameworks: Enhancing Stability Through Structural Disorder

Abstract: Metal-organic frameworks (Mofs) are intriguing host materials in composite electrolytes due to their ability for tailoring host-guest interactions by chemical tuning of the Mof backbone. Here, we introduce particularly high sodium ion conductivity into the zeolitic imidazolate framework ZIF-8 by impregnation with the sodium-salt-containing ionic liquid (iL) (na 0.1 eMiM 0.9)tfSi. We demonstrate an ionic conductivity exceeding 2 × 10 −4 S • cm −1 at room temperature, with an activation energy as low as 0.26 eV,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 60 publications
4
26
0
Order By: Relevance
“…12 This system has been previously studied with microcrystalline samples of ZIF-8 in our previous work. 3 NaIL was incorporated in the pores of both microporous and mesoporous samples of ZIF-8 as described in the experimental section and depicted in Fig.1, with the resulting composites being referred to as NaIL@ZIF-8micro and NaIL@ZIF-8meso.…”
Section: Preparation and Characterisation Of Il@mof Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…12 This system has been previously studied with microcrystalline samples of ZIF-8 in our previous work. 3 NaIL was incorporated in the pores of both microporous and mesoporous samples of ZIF-8 as described in the experimental section and depicted in Fig.1, with the resulting composites being referred to as NaIL@ZIF-8micro and NaIL@ZIF-8meso.…”
Section: Preparation and Characterisation Of Il@mof Compositesmentioning
confidence: 99%
“…Pellet mass g 1.07x10 -2 1.15x10 -2 Micropore + mesopore volume cm 3 6.85x10 -3 1.01x10 -2 Micropore volume cm 3 6.67x10 -3 4.49x10 -3 Mesopore volume cm 3 1.82x10 -4 5.59x10 -3 RT ionic conductivity S cm -1 1.6x10 -5 8.4x10 -6 RT pellet resistance Ω 849.7 1289.4 RT ionic conductance per total pore volume S cm -3 1.72x10 -1 7.70x10 -2 RT ionic conductance per micropore volume S cm -3 1.77x10 -1 1.73x10 -1…”
Section: Unit Nail@zif-8micro Nail@zif-8mesomentioning
confidence: 99%
See 1 more Smart Citation
“…These conductivity values were slightly lower than that of the Li + analogs (σ = 3.8 © 10 ¹7 S cm ¹1 for EHU1(Sc,Li) and 4.2 © 10 ¹4 S cm ¹1 for EHU1(Sc,Li)¢LiBF 4 ) at approximately room temperature. However, the activation energy of the Na + electrolyte (E a = 0.64 eV), which is higher than that of the Li + electrolyte (E a = 0.25 eV), led to a higher Na + conduction than Li + conduction at temperatures over 70°C, reaching a superionic 119 They selected ZIF-8 (Zn(MeIM) 2 ) with a pore size of ³3.4 ¡ as the host framework and a mixture of NaTFSI and EMIM-TFSI as the Na-doped IL. They confirmed that the composite electrolyte exhibited a high conductivity of ³2 © 10 ¹4 S cm ¹1 at room temperature, with a low activation energy of 0.26 eV.…”
Section: Na + and K + Conductorsmentioning
confidence: 92%
“…In addition, long-term ball milling may also cause the MOF structure to collapse, lose its periodic structure, and become amorphous [84,85], which is difficult to achieve in a solution phase reaction. The ball milling method can also make it more convenient to combine MOFs and other materials to form binary or even multiple composite materials [18,[86][87][88][89][90][91][92][93], such as GO/MOFs composites [94][95][96][97][98][99] Cu-BTC with truncated octahedral shape, and showed significantly reduction of reaction time and effectively improvement of yield [78].…”
Section: Comparison Of Ball-milling and Solution Methodsmentioning
confidence: 99%